Characteristics and sintering mechanisms of iron ores with a high proportion of high-Al2O3 limonite - Liang, Zhikai (2023)
In this study, a sintering test of high-alumina limonite from Indonesia, matched with an appropriate magnetite concentration, is performed. The sintering yield and quality index are effectively improved by optimizing the ore matching and regulating the basicity. For the optimal coke dosage of 5.8% and basicity of 1.8, the tumbling index of the ore blend is found to be 61.5% and the productivity is 1.2 t/(h·m2). The main liquid phase in the sinter is the silico-ferrite of calcium and aluminum (SFCA), followed by a mutual solution, both of which maintain the sintering strength. However, when the basicity is increased from 1.8 to 2.0, the production of SFCA is found to increase gradually, whereas the mutual solution content decreases dramatically. A metallurgical performance test of the optimal sinter sample demonstrates that the sinter can meet the requirements of small- and medium-sized blast furnace smelting, even for high-alumina limonite ratios of 60.0-65.0%, thereby greatly reducing the sintering production costs. The results of this study are expected to provide theoretical guidance for the practical high-proportion sintering of high-alumina limonite.